Trifluoromethyl chloroformate, CIC(O)OCF3: Structure, conformation, and vibrational analysis studied by experimental and theoretical methods - Erben, Mauricio Federico (2004)
The gas phase conformational properties and geometric structure of trifluoromethyl chloroformate, CIC(O)-OCF3, have been studied by vibrational spectroscopy (IR (gas), IR (matrix), and Raman (liquid)), gas electron diffraction (GED), and quantum chemical calculation (HF, B3LYP and MP2 methods with 6-311G* basis sets). The molecule exhibits only one form having Cs symmetry with synperiplanar orientation of the O-C single bond relative to the C=O double bond. If heated Ar:CIC(O)OCF3 mixtures are deposited as a matrix at 14 K, bands appear in the IR spectra which are assigned to the anti form. At room temperature, the contribution of the anti rotamer is estimated to be less than 1%. This high energy conformer is not observed in the GED experiment. The structure of solid CIC(O)OCF3 was determined by X-ray diffraction analysis from crystals obtained at low temperature, using a miniature zone melting procedure. The molecule crystallizes forming a dimeric structure belonging to the monoclinic crystal system and adopts the P21/n spatial group. Furthermore, we report the structure of the similar molecule trifluoroacetyl chloride. CF3C(O)Cl, in its crystalline phase by using the same method.